The Role Of Game Methods In Developing Speech And Literacy Of Primary Students (Journal of Pedagogical Inventions and Practices, 2026)
This article discusses the pedagogical importance of game methods in developing speech and literacy of primary school students. It also analyzes the role of didactic games in the educational process, their effectiveness in developing independent thinking, oral and written speech of students. Practical recommendations are given on the use of game methods in the classroom.